How to tackle the crisis in architectural education: Truth or Dare? (EAAE Annual Conference Proceedings, 2023)
Architectural practice is influenced by all the dynamics of daily life, such as climate change, pandemics, political changes, economic issues, globalization, and social inequalities, so the roles and responsibilities of the architect have also changed. As a result, the practice of architecture and the discipline of architecture has been compressed into a narrow field, and it can be called a crisis.